2016
DOI: 10.1140/epja/i2016-16094-1
|View full text |Cite
|
Sign up to set email alerts
|

A simplified BBGKY hierarchy for correlated fermions from a stochastic mean-field approach

Abstract: The stochastic mean-field (SMF) approach allows to treat correlations beyond mean-field using a set of independent mean-field trajectories with appropriate choice of fluctuating initial conditions. We show here, that this approach is equivalent to a simplified version of the Bogolyubov-BornGreen-Kirkwood-Yvon (BBGKY) hierarchy between one-, two-, ..., N-body degrees of freedom. In this simplified version, one-body degrees of freedom are coupled to fluctuations to all orders while retaining only specific terms … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…In a series of works, it was shown that it surprisingly well accounts for correlations beyond mean-field [37][38][39] while treating properly the dynamic close to a spontaneous symmetry breaking [38]. It is also able to include approximately many-body correlation to all orders by connecting the evolution to the BBGKY hierarchy [40]. Some formal and practical aspects are reviewed in Ref.…”
mentioning
confidence: 99%
“…In a series of works, it was shown that it surprisingly well accounts for correlations beyond mean-field [37][38][39] while treating properly the dynamic close to a spontaneous symmetry breaking [38]. It is also able to include approximately many-body correlation to all orders by connecting the evolution to the BBGKY hierarchy [40]. Some formal and practical aspects are reviewed in Ref.…”
mentioning
confidence: 99%
“…New stochastic extensions have been recently proposed for time-dependent quantum approaches [54,55]. A possibility is to inject quantum and/or thermal fluctuations just in the initial conditions of TDHF calculations, leading to a spread of dynamical trajectories and corresponding variances of physical observables.…”
Section: Theoretical Description Of Collision Dynamicsmentioning
confidence: 99%
“…As anticipated above, if a suited stochastic approach is adopted, simplified higher-order contributions to the dynamics are taken into account even though not explicitly implemented. Already within a firstorder-truncation scheme, it was found that a stochastic approach, including fluctuations only in the initial conditions, can be used to restore all the BBGKY missing orders approximately [54], and generate large-amplitude fluctuations; in this case, a coherent ensemble of mean-field states is propagated along different trajectories from an initial stochastic distribution. Such scheme, which appears appropriate in low-energy framework, is however insufficient to address highly dissipative regimes.…”
Section: Semi-classical Stochastic Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…[23]). In particular, correlations beyond the kinetic-equation level (or, equivalently, the upper orders beyond two-body correlations in a BBGKY hierarchy [24]) are introduced in full phase-space continuously in time. Such correlations are introduced by letting collide phase-space portions of extended size, large enough that the occupancy variance in h 3 cells corresponds to the scattering of two nucleons, and by simultaneously imposing that the Pauli blocking of initial and final states is nowhere violated over the full phase-space extension.…”
Section: -Modelling Volume and Surface Fluctuations: From Nuclear Mat...mentioning
confidence: 99%